I came as a stranger : the Underground Railroad - Prince, Bryan (Tundra Books ; Tundra Books of Northern New York, 2004)
Examines the history of the Underground Railroad, a network of people and safe refuges by which escaped slaves made their way north to freedom, focusing on the role of Canada in helping the fugitives create new, independent lives.